PERBANDINGAN PENDIDIKAN KARAKTER DI INDONESIA DAN JEPANG: PENDEKATAN, TANTANGAN, DAN SOLUSI - Hasanah, Nur Wahidatul; Zulaikah, Lutfi Dwi; Hasanah, Imroatul (Jurnal Multidisipliner Kapalamada, 2025)
This study compares character education in Indonesia and Japan, providing recommendations for Indonesia. In Indonesia, character education focuses on religious values, Pancasila, and national culture, while Japan emphasizes social values such as responsibility and cooperation in daily life. The research uses a qualitative method with a literature review approach, analyzing books, scholarly articles, and educational policies from both countries. The findings show that Indonesia faces challenges related to the uneven quality of education and the influence of globalization, while Japan struggles with balancing traditional values and global influences. This study recommends strengthening teacher training in Indonesia and integrating character education into daily school activities to address these challenges.